Comparison between Preventive Analgesia versus Postoperative Analgesia with Combined Paracetamol and Ketorolac in Laparoscopic Cholecystectomy - Ibraheem, Dr. Amassi Yakdhan (Academic Journal of Clinicians, 2024)
Background: Preventive analgesia refers to the use of medication or medical procedures that can effectively inhibit or block the painful response, with the goal of preventing the discomfort that typically occurs during a surgical treatment. Objective: To identify if there are differences in the control of postoperative pain when using preventive analgesia versus postoperative analgesia, managed with paracetamol + ketorolac in patients undergoing laparoscopic cholecystectomy elective. Patients and method: A Prospective controlled clinical trial included a sample of 70 patients randomly assigned into two groups (group 1 and 2) each included 35 patients to receive either preventive analgesia or paracetamol + ketorolac. Results: After 60 minutes, group 1 showed a significant reduction in the mean diastolic blood pressure of 4.2 mmHg, (P. value<0.05). A significant reduction in the mean numerical verbal scale of 0.71 point was also reported (P. value <0.05). The diastolic blood pressure at four hours indicated a mean difference of -3.5, with a significant p-value of 0.033. The incidence of nausea was less than that in group 2 (2.9% 8.6% ) respectively. Conclusion: Significant differences in the postoperative pain control, since patients with a preventive analgesia scheme have less postoperative pain compared to those to whom it grants them an immediate postoperative analgesia scheme.